Communicating choice: an exploration of mothers' experiences of birth. (14th March 2016) - Hallam, Jenny L.; Howard, Cristopher D.; Locke, Abigail; Thomas, Melissa
Abstract: Objective: This article gives an in-depth insight into the ways in which communication between midwives and the birthing woman shape the birth experience.Background: Birth is a significant life event for many women that can have profound, long-lasting effects on how they see themselves as women and mothers. Within the literature the importance of control over the birth experience and the support that the birthing woman receives from midwives is stressed.Methods: Six women who had recently given birth participated in one-to-one semi-structured interviews designed to explore the kinds of support they received before, during and after their birth. An inductive thematic analysis was employed in order to identify and explore key issues which ran throughout the interviews.Results: Within the interviews the importance of being an active mother, someone who made decisions in relation to her labour, was stressed. The analysis explores the ways in which communication style and compassionate care either enabled or prevented women from adopting the position of 'active' mother.Conclusion: It is argued that a personal connection with midwives and clear and open communication which places the birthing woman in a position of control are key to positive birth experiences.